Teachers versus the public : what Americans think about their schools and how to fix them - Peterson, Paul E.; Henderson, Michael B.; West, Martin R. (Brookings Institution Press, 2014)
A comprehensive exploration of 21st Century school politics, Teachers versus the Public offers the first comparison of the education policy views of both teachers and the public as a whole, and reveals a deep, broad divide between the opinions held by citizens and those who teach in the public schools. Among the findings:? Divisions between teachers and the public are wider and deeper than differences between other groups often thought to contest school policy, such as Republicans and Democrats, the young and the old, the rich and the poor, or African Americans and whites.>